Research on the influence of subjective factors on the occurrence of sports injuries in young volleyball players - Huang, Y.; Guba, V.; Yang, Z.; Rodin, A.; Bulykina, L. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the opinions of specialists on the factors determining the occurrence of sports injuries, as well as to propose a rehabilitation programme for the training of volleyball players in youth teams in Russia and China.